Utility of Boenninghausen’s Therapeutic Pocket Book - A Case Report (Homoeopathy for All, 2024)
This case demonstrates the  effectiveness of Boenninghausen’s  method and his less often used  repertory Boenninghausen’s  Therapeutic Pocket Book. This  is one of the earliest repertories  which based on primary proving  data source work of Hahnemann.  However, Therapeutic Pocket Book  is less used in practice because  of Kent’s influences. By using  Boenninghausen’s Therapeutic  Pocket Book we are able to reduce  the discomfort in patients with  urolithiasis.
Keywords: Boenninghausen’s Therapeutic Pocket Book; totality of symptoms; Repertory; SRA; SRN